CHARACTERIZATION OF THE WORLD VISION OF UNIVERSITY STUDENTS: A COMPARATIVE STUDY BETWEEN A BRAZILIAN AND PORTUGUESE UNIVERSITY - Rubia Salheb Fonseca; Amâncio Carvalho; Joaquim Escola; Armando Loureiro (Escola Superior de Educação de Paula Frassinetti, 2017)
UNESCO (2011) states that education should focus on students and consider them as protagonists of their learning and not as recipients of teaching. It is becoming increasingly clear in this and in numerous studies dealing with issues related to the learning processes of students, the importance of knowing more about their worldviews and trajectories. In order to identify aspects of the world view of the students. We used a quantitative and qualitative approach, a comparative, descriptive-correlational and cross-sectional study, using a questionnaire survey, Escala (Pagan, 2009). Sample of 1,240 students from two universities, 533 from the Portuguese University and 707 from the Brazilian University. Statistical analysis with SPSS (22.0) and content analysis using the word cloud.